Novel sustainable steel fiber reinforced preplaced aggregate concrete incorporating Portland limestone cement - Majed Ali Saleh; Zhihao Su; Ji Zhang (Scientific Reports, 2024)
Abstract This study proposes a novel approach by adding Portland limestone cement (PLC) to preplaced aggregate steel fiber reinforced concrete (PASFRC) to create a sustainable concrete that minimizes CO2 emissions and cement manufacturing energy usage. The method involves injected a flowable grout after premixing and preplacing steel-fibers and aggregates in the formwork. This study evaluates the mechanical properties of a novel sustainable concrete that uses PLC and steel fibers. To achieve the intended objective, long and short end-hooked steel fibers of 1%, 2%, 3%, and 6% were incorporated in PASFRC. Also, Analysis of variance (ANOVA) was used to examine the data. Results indicated that PLC and higher fiber doses increased the mechanical properties of PAC. At 90 days, PASFRC mixtures containing 6% long steel fibers demonstrated superior compressive, tensile, and flexural strengths, registering the highest values of 49.8 MPa, 7.7 MPa, and 10.9 MPa, respectively and differed by 188%, 166%, and 290%, respectively from fiberless PAC. The study confirmed the suitability and effectiveness of using PLC with steel fibers in PAC which significantly improved the mechanical properties of PASFRC. This was verified through analytical analysis and new empirical equations were proposed to predict the mechanical properties of PASFRC.